Implikasi Yuridis Pencabutan Keterangan Terdakwa Terhadap Kekuatan Pembuktian - Ridwan - (Fakultas Hukum Universitas Mataram, 2012)
Authentication is very important in the process of resolving criminal cases, because passing verification with valid evidence appliances, defendant can be convicted of the alleged criminal acts to his. One of the evidence contained in the Act is the defendant's testimony evidences, including defendant's (the suspect) testimony given in front of investigators. Defendant’s testimony given in front of investigators as one of the evidence appliances often revoked by defendant with various reasons. With the repeal, implicate to the strength of verification. If the revocation of defendant's testimony can be accepted by the judge, then it means that the defendant had given the untrue testimony in front of the investigator. As a result, defendant's testimony cannot be used as evidence and has no value or strength of evidence to prove the guilt of the defendant, so the defendant should be freed. Conversely, if the revocation of the defendant testimony cannot be accepted by the judge, it means the spoken testimonies of the defendants in front of the investigator was correct information and have evidentiary value, which consequently the defendant testimony can be used as evidence to prove the guilt of the defendant so the defendant should be sentenced.